Diethynylbenzo[1, 2‐b:4, 5‐b′]dithiophene‐based small molecule and cross‐conjugated copolymers for organic solar cells. Issue 4 (21st September 2016) - Xie, Ruihao; Xu, Rongguo; Liang, Yiming; Yin, Qingwu; Huang, Yunping; Ying, Lei; Huang, Fei; Cao, Yong
ABSTRACT: In this manuscript we reported the synthesis of diethynylbenzo[1, 2‐ b :4, 5‐ b ′]dithiophene(DEBDT)‐based small molecule BDTTIPS and three new cross‐conjugated copolymers PBDTE‐Th, PBDTE‐FBT, and PBDTE‐DPP that consist of DEBDT unit. The thermal, optophysical, and electronic properties of these materials were systematically investigated. The small molecule BDTTIPS exhibited higher absorption coefficient than the cross‐conjugated copolymers. The LUMO/HOMO energy levels of such three cross‐conjugated copolymers were −3.74/5.51, −3.77/–5.53, and −4.02/–5.58 eV as estimated from cyclic voltammetry measurements, which were lower than that of −3.63/–5.39 eV for the small molecule BDTTIPS. Due to the unique molecular structure and electronic properties of cross‐conjugated polymers, hole mobilities of PBDTE‐Th and PBDTE‐DPP were higher than that of BDTTIPS. Photovoltaic performances were investigated by fabricating organic solar cells with the configuration of ITO/PEDOT:PSS/donor:PC61 BM/Ca/Al. The small molecule chromophore BDTTIPS exhibited a power conversion efficiency of 4.19%, which was much higher than those obtained from devices based on conjugated polymers as the photoactive layer. These observations indicated that the DEBDT can be a promising building block for the construction of organic semiconducting materials for organic solar cell applications, and the rational molecular design was required for the attainment of high photovoltaic performances. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 660–671 Abstract : New small molecule BDTTIPS and three cross‐conjugated copolymers PBDTE‐Th, PBDTE‐FBT and PBDTE‐DPP based on this small molecule BDTTIPS were successfully synthesized. Their physical properties and photovoltaic characteristics were systematically investigated. Organic solar cells based on BDTTIPS exhibited a PCE of 4.19% as a result of a high‐degree of molecular ordering and preferable intrinsic phase separation with PC61 BM. However, organic solar cells based on the cross‐conjugated copolymers showed moderate photovoltaic performance due to the undesirable morphology of the copolymers.